2017
DOI: 10.1093/nar/gkx1067
|View full text |Cite
|
Sign up to set email alerts
|

miRTarBase update 2018: a resource for experimentally validated microRNA-target interactions

Abstract: MicroRNAs (miRNAs) are small non-coding RNAs of ∼ 22 nucleotides that are involved in negative regulation of mRNA at the post-transcriptional level. Previously, we developed miRTarBase which provides information about experimentally validated miRNA-target interactions (MTIs). Here, we describe an updated database containing 422 517 curated MTIs from 4076 miRNAs and 23 054 target genes collected from over 8500 articles. The number of MTIs curated by strong evidence has increased ∼1.4-fold since the last update … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
1,320
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 1,593 publications
(1,371 citation statements)
references
References 47 publications
10
1,320
1
3
Order By: Relevance
“…Four robust consensus molecular subtypes (CMSs) were identified, including a hypermutated, microsatellite unstable CMS1 subtype, a CMS2 marked by WNT and MYC signaling activation, a CMS3 showing evident metabolic dysregulation, and a CMS4 with marked activation of transforming growth factor-β signaling. Through characterizing the subtypes of CRC with transcriptomics approaches, this study revealed convergent pathway dependencies in thousands of cases, and proposed a classification system with clear biological interpretability, which could prove useful for clinical stratification and targeted interventions [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Four robust consensus molecular subtypes (CMSs) were identified, including a hypermutated, microsatellite unstable CMS1 subtype, a CMS2 marked by WNT and MYC signaling activation, a CMS3 showing evident metabolic dysregulation, and a CMS4 with marked activation of transforming growth factor-β signaling. Through characterizing the subtypes of CRC with transcriptomics approaches, this study revealed convergent pathway dependencies in thousands of cases, and proposed a classification system with clear biological interpretability, which could prove useful for clinical stratification and targeted interventions [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…As a database, miRTarBase has accumulated more than 360, 000 miRNA-target interactions (MTIs), which were collected by manually surveying pertinent literature after systematic, natural language processing of the text to filter research articles related to the functional study of miRNAs [22]. TargetScan predicts the biological targets of miRNAs by searching for the presence of conserved 8mer, 7mer, and 6mer sites that match the seed region of each miRNA, as an option, predictions with only poorly conserved sites are also provided [23].…”
Section: Target Mrnas Of Demirnasmentioning
confidence: 99%
“…For the significantly up-regulated genes, the ARCHS4 (Lachmann et al, 2018), miRTarBase 2017 (Chou et al, 2018) and BioCarta 2016 (Rouillard et al, 2016) databases were used to determine the Transcription Factors, MiRNAs and Pathways associated with them respectively.…”
Section: Gene Set Enrichment Analysis (Gsea) For the Up-regulated Genesmentioning
confidence: 99%